E-government, education quality, internet access in schools, and tax evasion - Khalil Nimer; Ali Uyar; Cemil Kuzey; Friedrich Schneider (Cogent Economics & Finance, 2022)
The study examines whether e-government services reduce the prevalence of tax evasion. Importantly, the study also investigates whether education quality as captured by three proxies and internet connection in schools strengthens the negative relationship between e-government services and tax evasion. The period covered by the study is confined to the years from 2006 to 2017 due to the data availability and Time Fixed-Effects Panel Data Analysis was adopted as empirical methodology. The results confirmed the significance of e-government services in reducing tax evasion and the moderating role of education quality in this relationship. More specifically, while overall, education quality and the quality of business management schools were shown to reinforce the significant negative link between e-government and tax evasion, the quality of math education did not. Finally, internet connection in schools was also found to reinforce the negative association between e-government and tax evasion. For public administrations, e-government initiatives and services are strengthening the capacity to leverage online services in the public domain to enhance tax compliance. Education system designers can consider these results in shaping curricula, integrating taxation issues in curricula, and enabling more equitable and reliable internet access in schools.
Keywords: 330; E-government; education quality; internet connection; tax evasion